Prevalence of human papilloma virus (HPV) and its genotypes in cervical specimens of Egyptian women by linear array HPV genotyping test. Issue 1 (December 2016) - Youssef, Mohamed; Abdelsalam, Lobna; Harfoush, Reem; Talaat, Iman; Elkattan, Eman; Mohey, Abeer; Abdella, Rana; Farhan, Marwa; Foad, Hany; Elsayed, Abeer; Elkinaai, Naglaa; Ghaith, Doaa; et al.
Abstract Background The association of human papillomavirus (HPV) with cervical cancer is well established. Aim To investigate HPV genotype distribution and co-infection occurrence in cervical specimens from a group of Egyptian women. Methods A group of 152 women with and without cervical lesions were studied. All women had cervical cytology and HPV testing. They were classified according to cytology into those with normal cytology, with squamous intraepithelial lesions (SIL) and invasive squamous cell carcinoma (SCC). Cervical samples were analyzed to identify the presence of HPV by PCR, and all positive HPV-DNA samples underwent viral genotype analysis by means of LINEAR ARRAY HPV Genotyping assay. Results A total of 26 HPV types with a prevalence of 40.8 % were detected. This prevalence was distributed as follows: 17.7 % among cytologically normal females, 56.5, 3.2, and 22.6 % among those with LSIL, HSIL and invasive SCC respectively. Low-risk HPV types were detected in 81.8 % of the cytologically-normal women, in 5.7 % of those in LSIL women, and in 14.3 % of infections with invasive SCC, while no low-risk types were detected in HSIL. High-risk HPV types were detected in 18.2 % of infections in the cytologically normal women, 14.3 % of infections in LSIL, and in 21.4 % of invasive lesions. The probable and possible carcinogenic HPV were not detected as single infections. Mixed infection was present in 80 % of women with LSIL, in 100 % of those with HSIL, and in 64.3 % of those with invasive SCC. This difference was statistically significant. HPV 16, 18 and 31 were the most prevalent HR HPV types, constituting 41.9, 29.03 and 12.9 % respectively, and HPV 6, 62 and CP6108 were the most prevalent LR HPV types constituting 11.3, 9.7 and 9.7 % respectively. Conclusion These data expand the knowledge concerning HPV prevalence and type distribution in Egypt which may help to create a national HPV prevention program. HPV testing using the LINEAR ARRAY HPV Genotyping assay is a useful tool when combined with cytology in the diagnosis of mixed and non-conventional HPV viral types.